STRATEGI OPTIMALISASI BUMDES BERBASIS POTENSI LOKAL DI DESA WONGKO LAKUDO KABUPATEN BUTON TENGAH PROVINSI SULAWESI TENGGARA - Rais, Muhammad (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The village of Wongko Lakudo in Lakudo Subdistrict, Central Buton Regency, has significant natural resource potential, particularly in terms of marine products and cashews. However, this potential has not been optimally utilized by the Village-Owned Enterprise (BUMDes). This community service activity aims to formulate and implement an optimization strategy for the BUMDes based on local potential to enhance the economic self-reliance and well-being of the village community. The method used is a participatory approach through several stages: problem observation, mapping of local potential, training in business management and digital marketing, business plan development, socialization, and monitoring and evaluation. The activity was carried out collaboratively with village partners, BUMDes management, community leaders, and local business actors. The results of the activity showed an increase in the capacity of BUMDes management in business management, business plan development, and financial management, the creation of a local potential map, and increased participation and synergy among village stakeholders.